Phosphogypsum and aeolian sand synergistically cured road subgrade filler and preparation method thereof
Through road subgrade fillers that are coordinated solidified by phosphogypsum and wind-abundant sand, and perthion gypsum slag cement as cementitious material, the problem of using sand resources for the desert environment is solved, and efficient, environmentally friendly and economical road subgrade filling effect is achieved.
Patent Information
- Application Number
- CN202411799790.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-09
AI Technical Summary
The prior art is difficult to effectively utilize wind-accumulated sand resources in desert environments as roadbed filling materials, and the use of traditional cement increases greenhouse gas emissions and production costs.
The roadbed filler that is coordinated with phosphogypsum and wind-accum sand is used to cure the roadbed filler. The perthion gypsum slag cement is used as the cementing material. The content of phosphogypsum and wind-accum sand is exceeded 80%, achieving comprehensive utilization of high dosage.
It improves the water retention and viscosity of wind-stacked sand, reduces material production and transportation costs, reduces greenhouse gas emissions, and meets the strength and performance requirements of different application scenarios.
Smart Images

Figure CN119707427A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of road subgrade materials, and in particular relates to a road subgrade filler that is synergistically solidified with phosphogypsum and aeolian sand, and a preparation method thereof. Background Art
[0002] In recent years, many highways around the edge of the desert and oasis areas are being built. However, due to the special characteristics of the desert environment, such as high temperature, dryness and frequent wind and sand, conventional road construction materials are difficult to meet construction needs. In addition, high-quality gravel materials need to be transported long distances from distant areas, which undoubtedly increases the cost and difficulty of construction. Therefore, how to turn the abundant local wind-blown sand resources into roadbed filling materials is a technical problem that needs to be solved urgently.
[0003] Persulfated phosphogypsum slag cement is a new type of unburned cementitious material, mainly composed of wet-ground modified phosphogypsum, granulated blast furnace slag powder, steel slag and silicate clinker mixed powder. Its preparation principle is mainly based on the combined action of sulfate and alkaline activator to stimulate the activity of slag, thereby initiating a reaction to generate a large amount of CSH gel and calcium sulfonate, which tightly wrap and connect the phosphogypsum particles to form a three-dimensional network space structure. The research and development goal of this cement is to solve the problem of large-scale accumulation of phosphogypsum and effectively utilize industrial waste slag, which is in line with the economic development trend of energy conservation and emission reduction. Compared with traditional cement, persulfated phosphogypsum slag cement not only exhibits excellent mechanical strength, but also has excellent sulfate corrosion resistance. In view of these significant advantages, persulfated phosphogypsum slag cement is being widely used in various engineering projects in freshwater and seawater environments, and can be used as a curing agent for roadbed fill. However, there is a gap in the research of cementitious materials for reinforcing aeolian sand.
[0004] Chinese patent publication number CN110204299B discloses a method for preparing a low-shrinkage and high-strength aeolian sand roadbed material, in which aeolian sand is used as the main material, and its content accounts for between 74% and 78% of the total mass; cement is used as a binder, and its proportion is between 6% and 8%; nanomaterials are used as reinforcing agents, and their addition amount is in the range of 1.5% to 2.5%; polyvinyl alcohol is used as a modifier, and its content is controlled between 0.1% and 0.5%; polymer emulsion is used as a stabilizer, and its proportion is between 0.2% and 0.8%; water glass is used as a curing agent, and its addition amount is between 0.5% and 1.2%; and the rest is water, which is used to adjust the overall performance of the material. It is worth noting that in this technical solution, cement is used as the main cementitious material, however, this choice inevitably leads to an increase in greenhouse gas emissions. In addition, given the relatively high cost of raw materials involved in this technical solution, the roadbed material prepared by this solution does not have a significant advantage in terms of economic benefits.
[0005] At present, there are few reports on the use of phosphogypsum and aeolian sand to synergistically solidify road subgrade fillers for desert highway construction. Summary of the invention
[0006] The purpose of the present invention is to address the deficiencies in the prior art and provide a road subgrade filler that is synergistically solidified with phosphogypsum and aeolian sand and a preparation method thereof, wherein phosphogypsum and aeolian sand are used to replace soil, and the water retention and cohesion are improved compared to aeolian sand, and the mixed soil is easier to compact. The properties of the mixed soil are between silt and silty clay, and a high-dosage comprehensive utilization of phosphogypsum and aeolian sand is achieved. The content of phosphogypsum and aeolian sand in the total roadbed filler material exceeds 80%.
[0007] To achieve the above object, the present invention adopts the following technical solution:
[0008] The first aspect of the present invention is to provide a road subgrade filler in which phosphogypsum and aeolian sand are synergistically solidified, wherein the road subgrade filler is prepared from persulfated phosphogypsum slag cement, a first modified phosphogypsum, aeolian sand and water, wherein the total mass of the first modified phosphogypsum and aeolian sand accounts for no less than 80% of the mass fraction of the road subgrade filler, the mass ratio of the first modified phosphogypsum to the aeolian sand is (3:1) to (1:3), and the persulfated phosphogypsum slag cement is prepared from a second modified phosphogypsum, slag powder and ordinary Portland cement.
[0009] Furthermore, the first modified phosphogypsum and the second modified phosphogypsum are both wet-ground modified phosphogypsum, and the preparation process is as follows: by weight, 92 to 95 parts of original phosphogypsum, 4 to 6 parts of slag powder and 2 to 3 parts of general-purpose Portland cement are mixed and wet-ground at a water-cement ratio of 0.42 to 0.47, and then allowed to stand for aging to obtain a modified phosphogypsum slurry, which is then dried.
[0010] Furthermore, the aeolian sand is aeolian sand from the Tengger Desert in Inner Mongolia Autonomous Region, with a particle size between 0.08 mm and 0.80 mm, and an effective particle size d 10 The average particle size is 0.081 mm. 50 The particle size d is 0.146 mm. 60 and d 30 They are 0.171mm and 0.115mm respectively.
[0011] Furthermore, in the persulfated phosphogypsum slag cement, the content of the second modified phosphogypsum is 40 to 50 parts by weight, the content of slag powder is 40 to 50 parts by weight, and the content of ordinary cement is 4 to 6 parts by weight.
[0012] Furthermore, the slag powder is S95 granulated blast furnace slag powder, the main components of which are SiO2, Al2O3 and MgO.
[0013] Furthermore, the density of the P.O42.5 ordinary Portland cement is 3.077 g / cm 3 , with a specific surface area of 358m 2 / kg, the main components are CaO, SiO2, Fe2O3 and Al2O3, and the main minerals are tricalcium silicate, dicalcium silicate, tricalcium aluminate and tetracalcium aluminoferrite.
[0014] Furthermore, the persulfate gypsum slag cement is added by external mixing method, and the content thereof ranges from 6% to 15%.
[0015] Furthermore, the first modified phosphogypsum and aeolian sand are used as aggregates, and the proportion of aeolian sand in the aggregate is between 0.25 and 0.75.
[0016] The second aspect of the present invention is to provide a method for preparing the above-mentioned phosphogypsum aeolian sand co-solidified road subgrade filler, comprising the following steps:
[0017] S1. Preparation of aggregate: crush the larger agglomerates in the wet-ground modified phosphogypsum, put them into an oven and dry them at 55°C to 60°C for 48h to 60h, and then pass them through a 0.6mm pore size sieve to obtain the treated phosphogypsum;
[0018] Aeolian sand within different particle size ranges is screened, and after weighing according to the determined aeolian sand particle group gradation, the aeolian sand is mixed evenly with the graded particle group to obtain aeolian sand;
[0019] S2. Preparation of persulfated phosphogypsum slag cement: wet-ground modified phosphogypsum, granulated blast furnace slag powder and ordinary Portland cement are mixed in a preset ratio, and then put into a cement paste mixer to ensure that the total water-cement ratio is 0.42-0.47 and stirred to obtain persulfated phosphogypsum slag cement;
[0020] S3. Dry mixing: Mix the aggregate phosphogypsum and aeolian sand evenly according to a preset ratio, pour into a mortar mixer and stir for 3 to 7 minutes to obtain a first mixture.
[0021] S4. Wet mixing: Pour persulfate gypsum slag cement and water into a mixer according to a preset ratio, stir at a speed of 500 r / min to 700 r / min for 5 to 10 minutes until uniform, to obtain a second mixture.
[0022] S5, molding and curing: spreading and compacting the second mixture obtained in step S4, and performing heat preservation and moisture preservation curing to obtain the road subgrade filler in which the phosphogypsum and aeolian sand are synergistically solidified.
[0023] Further, in step S4, the moisture content of 15.064% to 16.274% and the maximum dry density of 1.717 g / cm2 determined by the compaction test are 3 ~1.784g / cm 3 .
[0024] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0025] (1) The present invention provides a phosphogypsum and aeolian sand synergistically solidified road subgrade filler, which replaces soil with phosphogypsum and aeolian sand. Compared with aeolian sand, the mixed soil has improved water retention and cohesion and is easier to compact. The properties of the mixed soil are between silt and silty clay, achieving high-content comprehensive utilization of phosphogypsum and aeolian sand. The content of phosphogypsum and aeolian sand in the total roadbed filler material exceeds 80%.
[0026] (2) The different composition design ratios of the high-doped phosphogypsum and aeolian sand synergistic solidifying materials provided by the present invention can meet the precise design of the composition of the new solidifying materials required by different application scenarios. The 14-day unconfined compressive strength of the roadbed filler cured at room temperature is 0.450MPa~0.760MPa, and the 28-day unconfined compressive strength is 0.566MPa~1.556MPa, which meets the relevant requirements for roadbed construction strength and working performance in JTG / T3610-2019 "Technical Specifications for Highway Roadbed Construction".
[0027] (3) The present invention uses persulfated phosphogypsum slag cement as a cementing material to solidify the phosphogypsum aeolian sand mixed soil. The cement is mixed with a large proportion of phosphogypsum (50%), slag powder (45%) and ordinary Portland cement (5%), which not only significantly reduces greenhouse gas emissions and achieves the goal of waste resource utilization, that is, using waste to treat waste, but also fully taps the economic value of phosphogypsum.
[0028] (4) The road subgrade filler solidified by the synergistic solidification of phosphogypsum and aeolian sand of the present invention is particularly suitable for application in desert environments. This technology makes full use of the aeolian sand resources along the highways in arid desert areas, and uses aeolian sand as an important component of aggregate to replace traditional roadbed fill materials, thereby significantly reducing the production cost and transportation cost of the materials. At the same time, by synergistically utilizing industrial waste such as phosphogypsum and slag powder, it achieves effective recycling of resources and creates considerable economic benefits. This technology shows strong market promotion and application potential, indicating that it will play an important role in related fields.
[0029] (5) The preparation process provided by the present invention is extremely simple. It only needs to wet-grind the original phosphogypsum and then fully mix the modified phosphogypsum and aeolian sand aggregate in a predetermined ratio, then add the pre-set ratio of persulfated phosphogypsum slag cement and water, stir evenly again and perform molding and curing, and a new type of solidified material that can meet the needs of various application scenarios can be produced. In this preparation process, the proportion of the externally added cementitious material can be flexibly adjusted within the range of 6% to 15%, with an adjustment gradient of 3%; at the same time, the proportion of aeolian sand in the aggregate can also be gradually increased within the range of 0 to 1, with an adjustment gradient of 0.2. By accurately controlling the ratio between the components, the generation of its hydration products can be effectively regulated, and then, starting from the hydration mechanism level, a phosphogypsum aeolian sand synergistic solidified road subgrade filler that meets the strength and performance requirements of various roads can be prepared. It is particularly worth mentioning that the preparation process does not require complex treatment such as calcination of phosphogypsum, which greatly simplifies the construction process and improves construction efficiency.
[0030] (6) The present invention uses persulfated phosphogypsum slag cement to solidify phosphogypsum aeolian sand aggregate for road subgrade filling. This solidification process does not rely solely on a single mechanism, but is the result of the synergistic and combined action of chemical mechanisms and physical actions. Specifically, the formation of its mechanical strength involves multiple stages, including physical compaction process, chemical excitation and ion exchange, gel and calcium aluminate bonding, agglomeration effect and physical filling process, which jointly promote the strength development of the solidified body.
[0031] Physical compaction: After the phosphogypsum and aeolian sand are compacted and solidified into roadbed filler, the internal structure of the solidified body shows the close fit and mutual extrusion between the gypsum crystal particles and the aeolian sand particles. The phosphogypsum crystals are mostly plate-like or columnar in shape, but there are still some areas where tiny gaps remain between the gypsum crystal particles.
[0032] Chemical excitation and ion exchange: Under alkaline environmental conditions, active components such as SiO2, Al2O3 and CaO in the raw materials undergo a chemical excitation process accompanied by ion exchange reactions, thereby generating a honeycomb network of hydrated calcium silicate gel with cementing properties; at the same time, some gypsum crystals inside the phosphogypsum particles are converted into needle-shaped calcium sulfonate crystals under the action of sulfate excitation effect.
[0033] Bonding effect between gel and ettringite: Under the action of bonding force, the honeycomb-like three-dimensional network gel is interconnected and aggregated into a large number of compact flocculent gel aggregates. These aggregates are tightly adhered to the surfaces of gypsum crystal particles and aeolian sand particles. At the same time, the needle-shaped ettringite is also firmly adhered to the surfaces of these particles, together constructing a stable structural system.
[0034] Agglomeration: A large amount of gel polymers gradually achieve comprehensive coverage and encapsulation of phosphogypsum particles and aeolian sand particles by tightly adhering to the surfaces of these particles. In this process, the phosphogypsum particles and aeolian sand particles wrapped by the gel are interconnected to form a new layer of gel bonding. This bonding layer still has the function of connecting the phosphogypsum particles and the aeolian sand particles. Through the continuous cycle bonding process, agglomerates with particle grading characteristics are gradually formed. The particles in these agglomerates are of different sizes and are embedded in each other, together constructing a stable spatial skeleton structure.
[0035] Physical filling: A large number of remaining phosphogypsum particles and aeolian sand particles are tightly embedded in each other, filling the gaps in the aggregate skeleton. At the same time, tiny needle-shaped ettringite crystals fill the gaps between the gypsum crystals, together constructing a dense skeleton space structure.
[0036] The solidification mechanism of persulfated phosphogypsum slag cement on phosphogypsum and aeolian sand mixed soil lies in the fact that it tightly bonds the phosphogypsum and aeolian sand particles through gelation, thereby forming a denser aggregate structure. In addition, the incompletely bonded phosphogypsum particles, aeolian sand particles and the generated ettringite act as filling materials to effectively fill the gaps in the structure, significantly improving the compactness of the mixed soil. The phosphogypsum particles not only support the skeleton structure of the solidified body, but also work together with the aeolian sand particles and ettringite to play an important role in optimizing the skeleton gap filling effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 is the XRD spectrum of the persulfate gypsum slag cement in the present invention;
[0038] Figure 2 The XRD spectrum of the phosphogypsum aeolian sand synergistically solidified road subgrade filler of the present invention;
[0039] Figure 3 This is a 7d microscopic morphology of the persulfated gypsum slag cement of the present invention;
[0040] Figure 4 This is a 28d microscopic morphology of the persulfated gypsum slag cement of the present invention;
[0041] Figure 5 This is a 7d microscopic morphology of the phosphogypsum aeolian sand synergistically solidified road subgrade filler of the present invention;
[0042] Figure 6 This is a 14d microscopic morphology of the phosphogypsum aeolian sand synergistically solidified road subgrade filler of the present invention;
[0043] Figure 7 This is a 28d microscopic morphology of the phosphogypsum aeolian sand co-solidified road subgrade filler of the present invention. DETAILED DESCRIPTION
[0044] In order to make the purpose, technical scheme and advantages of the present invention clearer, the specific embodiments of the present invention are further described in detail below in conjunction with specific examples and drawings. If no specific test method, instrument or condition is specified in the examples, it is carried out according to the technology or condition described in the literature in this field or according to the product instructions. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be obtained commercially.
[0045] The aeolian sand selected in the present invention is aeolian sand from the Inner Mongolia Autonomous Region, whose particle composition is mainly concentrated between 0.5 and 0.075 mm, accounting for as high as 90% to 95%, and its mechanical composition tends to be fine, with a large surface area, and a coefficient of unevenness Cu≤5, which is classified as poorly graded fine sand; this type of aeolian sand contains a small amount of clay particles, showing excellent water permeability and water stability, but weak water retention capacity, and the characteristics of aeolian sand conform to the characteristics of typical sandy soil. The main components of aeolian sand are rock debris, feldspar and quartz, and the total content of these three types of particles exceeds 90%, among which the content of quartz particles is the most significant, and its surface is relatively smooth, and the aeolian sand has the characteristics of weak alkalinity; in addition, the internal friction angle of aeolian sand is stable at about 39°, and the cohesion is almost negligible.
[0046] The present invention uses persulfated phosphogypsum slag cement to solidify the phosphogypsum aeolian sand mixed soil. The persulfated phosphogypsum slag cement is prepared from wet-ground modified phosphogypsum (PG), granulated blast furnace slag powder (S95) and P.O42.5 ordinary Portland cement. The composition of the phosphogypsum aeolian sand synergistically solidified road subgrade filler further integrates the above-mentioned persulfated phosphogypsum slag cement, phosphogypsum and aeolian sand three materials to ensure the stability and durability of the road subgrade.
[0047] The wet-ground modified phosphogypsum preparation process adopted in the present invention is as follows: by weight, 92 to 95 parts of original phosphogypsum, 4 to 6 parts of slag powder and 2 to 3 parts of general-purpose Portland cement are mixed and wet-ground at a water-cement ratio of 0.42 to 0.47, and the mixture is allowed to stand for aging to obtain a modified phosphogypsum slurry, which is then dried.
[0048] The persulfated phosphogypsum slag cement used in the present invention has a specific mass proportion of the components after precise proportion: wet-ground modified phosphogypsum accounts for 40% to 50% of the total mass, preferably 50%, granulated blast furnace slag powder accounts for 40% to 50%, preferably 45%, and ordinary Portland cement accounts for the remaining 4% to 6%, preferably 5%. After the above components are mixed, they are put into a cement paste mixer to ensure that they are stirred under the condition of a total water-cement ratio of 0.42 to 0.47.
[0049] The phosphogypsum selected in this embodiment is wet-ground modified phosphogypsum. The original phosphogypsum, slag powder and general silicate cement are mixed in a ratio of 45:1:2 under the condition of a water-cement ratio of 0.43, and then wet-ground for 1 hour and left to stand for 24 hours to obtain a modified phosphogypsum slurry. After drying, the modified phosphogypsum powder is obtained, and its specific surface area is 170.4m 2 / kg, in gray granular form, with a density of 2.35g / cm 3 The mass fraction of attached water is strictly controlled within the range of no more than 20%, while the mass fraction of CaSO4·2H2O is not less than 80%, the mass fraction of water-soluble P2O5 is limited to no more than 0.3%, and the mass fraction of water-soluble F - The mass fraction does not exceed 0.2%; through the X-ray fluorescence spectrometry (XRF) method, it is determined that the main chemical composition of the phosphogypsum is calcium oxide (CaO) and sulfur trioxide (SO3); further using the X-ray diffraction analysis (XRD) technology, it is confirmed that its main mineral component is calcium sulfate dihydrate (CaSO4·2H2O); the laser particle size analyzer is used to accurately measure the particle size distribution of the phosphogypsum, and its particle size is mainly concentrated in the range of 10 to 110 μm.
[0050] The slag powder selected in this embodiment is S95 grade granulated blast furnace slag powder, and its specific surface area is measured to be 424m 2 / kg, through X-ray fluorescence spectrometry (XRF) technology, it was determined that the main chemical components of the mineral powder are calcium oxide (CaO), aluminum oxide (Al2O3) and silicon dioxide (SiO2).
[0051] The P.O42.5 ordinary Portland cement selected in this embodiment has a density of 3.077 g / cm 3 , with a specific surface area of 358m 2 / kg, and its main chemical components were determined by X-ray fluorescence spectrometry (XRF) to be calcium oxide (CaO), silicon dioxide (SiO2), ferric oxide (Fe2O3) and aluminum oxide (Al2O3); further analysis showed that the main mineral components of the cement were tricalcium silicate (3CaO·SiO2), dicalcium silicate (2CaO·SiO2), tricalcium aluminate (3CaO·Al2O3) and tetracalcium aluminoferrite (4CaO·Al2O3·Fe2O3).
[0052] The aeolian sand selected in this example is the aeolian sand from the Tengger Desert in Inner Mongolia Autonomous Region as the research object. The particle size is between 0.08 mm and 0.80 mm. The effective particle size d 10 The average particle size is 0.081 mm. 50 The particle size d is 0.146 mm. 60 and d 30They are 0.171mm and 0.115mm respectively, the uniformity coefficient is 2.111, the curvature coefficient is 0.9555, and the grading is poor.
[0053] The chemical compositions of the phosphogypsum, slag powder and ordinary Portland cement used in this example are shown in Table 1.
[0054] Table 1
[0055]
[0056] The preparation of the roadbed filler of the phosphogypsum aeolian sand co-solidification of the present invention specifically comprises the following steps:
[0057] Step S1, preparation of wet-ground modified phosphogypsum: original phosphogypsum, slag powder and general silicate cement are mixed in a ratio of 45:1:2 at a water-cement ratio of 0.43, wet-ground for 1 hour and allowed to stand for 24 hours to obtain modified phosphogypsum slurry, and then dried to obtain modified phosphogypsum powder.
[0058] Step S2, treatment of phosphogypsum and aeolian sand: crushing larger lumps in the wet-ground modified phosphogypsum, drying the phosphogypsum in an oven at 55°C for 48 hours, and then passing the phosphogypsum through a 0.6 mm aperture sieve to obtain the treated phosphogypsum; spreading the yellow sand sample evenly for natural air drying, and after air drying, carefully screening the aeolian sand according to the preset particle size standard, i.e., the particle size is between 0.08 mm and 0.80 mm, and then accurately weighing the aeolian sand according to the established aeolian sand particle group grading requirements, wherein the effective particle size d 10 Set to 0.081 mm, average particle size d 50 The particle size d is 0.146 mm, and the particle size d is strictly controlled. 60 and d 30 They are 0.171mm and 0.115mm respectively. Finally, the weighed particle groups of each level are fully mixed to ensure uniformity, so as to prepare aeolian sand samples that meet the requirements.
[0059] Step S3, preparation of persulfated phosphogypsum slag cement: accurately weigh and fully mix the wet-ground modified phosphogypsum, granulated blast furnace slag powder and ordinary Portland cement in a mass ratio of 50:45:5, put the evenly mixed materials into a cement slurry mixer and ensure that they are stirred at a total water-cement ratio of 0.3 to prepare the required persulfated phosphogypsum slag cement.
[0060] Step S4, dry mixing: weigh phosphogypsum and aeolian sand aggregate according to a preset ratio and mix them in a stirring pot, and stir for 3 to 7 minutes until the mixture is uniform to obtain a first mixture.
[0061] Step S5, wet mixing: weigh the persulfate gypsum slag cement and water obtained in step S2 according to a preset ratio, pour them into a stirring pot, and stir for 3 to 10 minutes until they are uniform, to obtain a second mixture.
[0062] Step S6, molding and curing: the second mixture obtained in step S5 is spread and compacted to form, and heat-insulating and moisture-retaining curing is performed to obtain the phosphogypsum aeolian sand synergistically solidified road subgrade filler.
[0063] Example 1
[0064] Weigh the raw materials according to the following mass: the mass ratio of phosphogypsum and aeolian sand to aggregate is 100% and 0% respectively, and the amount of persulfated phosphogypsum slag cement is 6%. Weigh the composite materials according to the best moisture content of 16.341% and the maximum dry density of 1.708g / cm determined by the compaction test. 3 Weigh the water.
[0065] According to the specific method steps of the production process, the phosphogypsum aeolian sand synergistic solidification road subgrade filler was prepared, and its relevant properties were tested using the following test methods:
[0066] Unconfined compressive strength: Based on the determination of the California Bearing Ratio (CBR) value of the phosphogypsum aeolian sand co-solidified road subgrade filler, the unconfined compressive strength is used as one of the core indicators for evaluating its strength performance; this indicator can quickly and accurately reflect the strength characteristics of the specimen. By adjusting the proportion range of the phosphogypsum aeolian sand co-solidified road subgrade filler and preparing relevant specimens with a compaction degree of 96%, the unconfined compressive strength of the specimens was measured using two curing methods, room temperature sealing and 55°C sealing. This process aims to comprehensively and systematically analyze the mechanical properties of the filler.
[0067] Internal friction angle and cohesion: Set the vertical pressure as the horizontal axis and the shear strength as the vertical axis. Accurately mark the shear strength data points of each sample on the coordinate paper and connect these points with a straight line. The inclination angle of this straight line is the internal friction angle, and the intersection of the straight line and the vertical axis represents the cohesion.
[0068] Leachate pollutants: The release of harmful elements in the leachate of roadbed fillers has an important impact on the surrounding environment, especially the quality of groundwater. The "Surface Water Environmental Quality Standard" (GB3838-2002) and the "Groundwater Quality Standard" (GB / T14848-2017) have strict standards for the content of phosphorus (P), fluorine (F), cadmium (Cd), arsenic (As), lead (Pb) and chromium in groundwater. The leachate of roadbed fillers should meet the groundwater standards; immerse the standard specimens in water, take representative solution samples at the specified age for laboratory testing, and filter with a 0.45μm filter membrane before testing to obtain the leachate for test analysis.
[0069] The main performance indicators of the roadbed filler of phosphogypsum and aeolian sand co-solidified prepared in this example are tested according to the above test method and are as follows in Table 2:
[0070] Table 2.
[0071]
[0072] Example 2
[0073] Weigh the raw materials according to the following mass: the mass ratio of phosphogypsum and aeolian sand to aggregate is 100% and 0 respectively, and the amount of persulfated phosphogypsum slag cement is 15%. Weigh the composite materials according to the optimum moisture content of 16.262% and the maximum dry density of 1.717g / cm determined by the compaction test. 3 Weigh the water.
[0074] The main performance indicators of the phosphogypsum aeolian sand synergistically solidified road subgrade filler prepared in this example are tested according to the above test method and are as follows in Table 3:
[0075] Table 3.
[0076]
[0077] Example 3
[0078] Weigh the raw materials according to the following mass: phosphogypsum and aeolian sand account for 75% and 25% of the mass ratio of aggregate respectively, add 6% of persulfated phosphogypsum slag cement, weigh the composite materials, and determine the best moisture content of 16.262% and the maximum dry density of 1.717g / cm according to the compaction test. 3 Weigh the water.
[0079] The main performance indicators of the phosphogypsum aeolian sand synergistically solidified roadbed filler prepared in this example are tested according to the above test method and are shown in Table 4:
[0080] Table 4.
[0081]
[0082] Example 4
[0083] Weigh the raw materials according to the following mass: the mass ratio of phosphogypsum and aeolian sand to aggregate is 75% and 25% respectively, the amount of externally added persulfated phosphogypsum slag cement is 15%, weigh the composite materials, according to the best moisture content of 16.274% and the maximum dry density of 1.781g / cm determined by the compaction test 3 Weigh the water.
[0084] The main performance indicators of the phosphogypsum aeolian sand synergistically solidified road subgrade filler prepared in this example are tested according to the above test method and are shown in Table 5:
[0085] Table 5.
[0086]
[0087] Example 5
[0088] Weigh the raw materials according to the following mass: phosphogypsum and aeolian sand account for 50% and 50% of the aggregate mass respectively, add 6% of persulfated phosphogypsum slag cement, weigh the composite materials, and determine the optimum moisture content of 16.274% and the maximum dry density of 1.781g / cm according to the compaction test. 3 Weigh the water.
[0089] The main performance indicators of the phosphogypsum aeolian sand synergistically solidified roadbed filler prepared in this example are tested according to the above test method and are shown in Table 6:
[0090] Table 6.
[0091]
[0092] Example 6
[0093] Weigh the raw materials according to the following mass: phosphogypsum and aeolian sand account for 50% and 50% of the aggregate mass respectively, add 15% of persulfated phosphogypsum slag cement, weigh the composite materials, and determine the optimum moisture content of 16.064% and the maximum dry density of 1.784g / cm according to the compaction test. 3 Weigh the water.
[0094] The main performance indicators of the phosphogypsum aeolian sand synergistically solidified roadbed filler prepared in this example are tested according to the above test method and are shown in Table 7:
[0095] Table 7.
[0096]
[0097] Example 7
[0098] Weigh the raw materials according to the following mass: phosphogypsum and aeolian sand account for 25% and 75% of the mass ratio of aggregate respectively, add 6% of persulfated phosphogypsum slag cement, weigh the composite materials, and determine the optimum moisture content of 15.064% and the maximum dry density of 1.784g / cm according to the compaction test. 3 Weigh the water.
[0099] The main performance indicators of the phosphogypsum aeolian sand synergistically solidified roadbed filler prepared in this example are tested according to the above test method and are shown in Table 8:
[0100] Table 8.
[0101]
[0102] Example 8
[0103] Weigh the raw materials according to the following mass: phosphogypsum and aeolian sand account for 25% and 75% of the mass ratio of aggregate respectively, add 15% of persulfated phosphogypsum slag cement, weigh the composite materials, and determine the optimum moisture content of 15.064% and the maximum dry density of 1.784g / cm according to the compaction test. 3 Weigh the water.
[0104] The main performance indicators of the phosphogypsum aeolian sand synergistically solidified roadbed filler prepared in this example are tested according to the above test method and are shown in Table 9:
[0105] Table 9.
[0106]
[0107] Example 9
[0108] Weigh the raw materials according to the following mass: the mass ratio of phosphogypsum and aeolian sand to aggregate is 0 and 25% respectively, and the amount of persulfated phosphogypsum slag cement is 6%. Weigh the composite materials according to the best moisture content of 16.432% and the maximum dry density of 1.818g / cm determined by the compaction test. 3 Weigh the water.
[0109] The main performance indicators of the phosphogypsum aeolian sand synergistically solidified roadbed filler prepared in this example are tested according to the above test method and are shown in Table 10:
[0110] Table 10.
[0111]
[0112] Example 10
[0113] Weigh the raw materials according to the following mass: the mass ratio of phosphogypsum and aeolian sand to aggregate is 0 and 25% respectively, and the amount of sulphurized phosphogypsum slag cement is 15%. Weigh the composite materials according to the best moisture content of 15.910% and the maximum dry density of 1.823g / cm determined by the compaction test. 3 Weigh the water.
[0114] The main performance indicators of the phosphogypsum aeolian sand synergistically solidified roadbed filler prepared in this example are tested according to the above test method and are shown in Table 11:
[0115] Table 11.
[0116]
[0117] It can be concluded from Tables 2 to 11 that with the increase of the content of persulfated phosphogypsum slag cement and the content of phosphogypsum in the aggregate, the strength of the roadbed filler gradually increases; the early strength of the roadbed filler solidified by phosphogypsum aeolian sand under room temperature is low, and the later strength is high, up to 2217 kPa. The effective elements such as calcium and silicon in phosphogypsum and slag powder play a significant role in promoting the strength of the roadbed filler after hydration reaction, and make a great contribution to stabilizing the later strength; the cohesion and internal friction angle of the roadbed filler increase with the increase of the content of persulfated phosphogypsum slag cement, and increase with the increase of phosphogypsum in the aggregate when the content of cementitious materials is the same, which is related to the change law of unconfined compressive strength; the cohesion and friction angle of the preferred embodiment 3 are 55 kPa and 19.19° respectively. According to the "Highway Roadbed Design Code" (JTG D30-2023) shows that the structural surface type of the sample is a hard structural surface with good shear strength; when the amount of cementitious material is fixed, the phosphorus content in the leachate increases with the increase of the phosphogypsum content in the aggregate; the phosphorus content in the leachate in Examples 6 to 10 meets the Class V standard limit specified in the "Groundwater Environmental Quality Standard" (GB3832-2002). Phosphogypsum aeolian sand synergistic solidification road subgrade filler is most suitable for high temperature and low rainfall environments.
[0118] In order to better illustrate the superior performance of the phosphogypsum aeolian sand synergistically solidified road subgrade filler of the present invention, the applicant conducted the following research:
[0119] like Figure 1 As shown in the figure, it is the X-ray diffraction (XRD) spectrum of the persulfated phosphogypsum slag cement used in Examples 1 to 10. It can be observed that quartz occupies a dominant position in the mineral components, followed by gypsum particles, while the content of ettringite is relatively low; quartz as an inherent mineral component in the raw material is retained during the hydration reaction, gypsum particles are one of the main minerals remaining after the hydration reaction, and ettringite is a product jointly generated by phosphogypsum, blast furnace slag powder and ordinary Portland cement during the hydration reaction.
[0120] like Figure 2 As shown, it is the XRD superposition comparison diagram of the phosphogypsum aeolian sand co-solidified road subgrade filler and the phosphogypsum raw material prepared in Examples 1 to 6. It can be observed that the phosphogypsum aeolian sand co-solidified road subgrade filler also contains gypsum particles, quartz and ettringite, but the highest content is gypsum, followed by quartz, and the lowest peak is ettringite.
[0121] Depend on Figure 1 , Figure 2It can be seen that the mineral phase that occupies a dominant position in the phosphogypsum aeolian sand co-solidified road subgrade filler has changed from quartz to gypsum compared with persulfated phosphogypsum slag cement. The phosphogypsum in the aggregate will also participate in the hydration reaction process, but its hydration degree is significantly lower than that of the phosphogypsum in persulfated phosphogypsum slag cement.
[0122] like Figure 3 and Figure 4 As shown in the figure, the microscopic morphology of persulfated phosphogypsum slag cement at the ages of 7 days and 28 days respectively. It can be seen that part of the phosphogypsum participates in the hydration reaction, and the generated needle-shaped calcium sulfonate and hydrated calcium silicate gel and other products have played a positive role in promoting the strength growth of the material. Moreover, with the increase of age, the originally irregularly grown needle-shaped calcium sulfonate gradually aggregates and grows, and is interlaced, cemented and adhered to the phosphogypsum that does not participate in the hydration reaction, forming a more stable and dense structure.
[0123] like Figure 5 As shown, it is a microscopic morphology of the phosphogypsum aeolian sand co-solidified road subgrade filler of the present invention at the age of 7 days. It can be observed that the gypsum particles and quartz particles are in a tightly compacted state, and the particles are irregularly filled with each other to form a dense structure. The phosphogypsum is mostly in the form of plates or columns, which further enhances the stability of the filler; partially hydrated calcium silicate gel and calcium sulfonate are generated in the gaps between the particles and on the surface of the particles, which improves the overall strength and durability of the roadbed filler.
[0124] like Figure 6 As shown in the figure, it is a microscopic morphology of the phosphogypsum aeolian sand co-solidified road subgrade filler of the present invention at the age of 14 days. It can be seen that the active ingredients such as SiO2, Al2O3 and CaO in the raw materials successfully generate a honeycomb network hydrated silicate gel with significant cementing properties through the ion exchange mechanism under the conditions of an alkaline environment, and the gypsum crystals in some phosphogypsum particles form needle-shaped calcium aluminate crystals under the stimulation of sulfate.
[0125] like Figure 7 As shown, it is a microscopic morphology of the phosphogypsum aeolian sand co-solidified road subgrade filler of the present invention at the age of 28 days. It can be seen that individual spherical agglomerates are formed by gel-adhered phosphogypsum crystals and aeolian sand particles, and the hydrated calcium silicate gel bonds the individual agglomerates to form addition polymers.
[0126] Depend on Figure 6 and Figure 7It can be seen that a large number of gel polymers gradually achieve full coverage and wrapping of the particles by tightly adhering to the surface of phosphogypsum particles and aeolian sand particles. The phosphogypsum particles and aeolian sand particles wrapped by the gel further form a new gel bonding layer through the bonding effect of the gel. This bonding layer still has the function of connecting phosphogypsum and aeolian sand particles, thus promoting the generation of a cycle process: the particles are constantly bonded by the gel, gradually building up agglomerates with particle grading characteristics. The particles in these agglomerates are of different sizes, they are interlocked and squeezed with each other, and together they build a spatial skeleton structure. At the same time, ettringite crystals, excess gypsum particles and aeolian sand particles fill the gaps in the skeleton structure, and finally form a dense and stable overall structure.
[0127] In summary, by regulating the addition amount of persulfated phosphogypsum slag cement and the proportion of phosphogypsum in aggregate, the synergistic effect of phosphogypsum and aeolian sand can be achieved to form a more stable internal structure in the road subgrade filler. By effectively controlling the generation of hydration products, a phosphogypsum and aeolian sand synergistically solidified road subgrade filler that can meet the strength and other performance requirements of various types of roads can be fundamentally designed to meet the diverse road performance requirements and thus adapt to practical applications in different construction scenarios.
[0128] In the absence of conflict, the above embodiments and features in the embodiments may be combined with each other.
[0129] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A roadbed filler solidified by phosphogypsum and aeolian sand, characterized in that: The road subgrade filler is prepared from persulfated phosphogypsum slag cement, a first modified phosphogypsum, aeolian sand and water, wherein the total mass of the first modified phosphogypsum and the aeolian sand accounts for no less than 80% of the mass fraction of the road subgrade filler, the mass ratio of the first modified phosphogypsum to the aeolian sand is (3:1) to (1:3), and the persulfated phosphogypsum slag cement is prepared from a second modified phosphogypsum, slag powder and ordinary Portland cement.
2. The road subgrade filler as claimed in claim 1, characterized in that: The first modified phosphogypsum and the second modified phosphogypsum are both wet-ground modified phosphogypsum, and the preparation process is as follows: by weight, 92 to 95 parts of original phosphogypsum, 4 to 6 parts of slag powder and 2 to 3 parts of general-purpose Portland cement are mixed and wet-ground at a water-cement ratio of 0.42 to 0.47, and then allowed to stand for aging to obtain a modified phosphogypsum slurry, which is then dried.
3. The road subgrade filler as claimed in claim 2, characterized in that: The aeolian sand is aeolian sand from the Tengger Desert in Inner Mongolia Autonomous Region, with a particle size between 0.08 mm and 0.80 mm. 10 The average particle size is 0.081 mm. 50 The particle size d is 0.146 mm. 60 and d 30 They are 0.171mm and 0.115mm respectively.
4. The road subgrade filler as claimed in claim 2, characterized in that: In the persulfated phosphogypsum slag cement, by weight, the content of the second modified phosphogypsum is 40 to 50 parts, the content of slag powder is 40 to 50 parts, and the content of ordinary cement is 4 to 6 parts.
5. The road subgrade filler as claimed in claim 4, characterized in that: The slag powder is S95 granulated blast furnace slag powder, and its main components are SiO2, Al2O3 and MgO.
6. The road subgrade filler as claimed in claim 5, characterized in that: The density of the P.O42.5 ordinary Portland cement is 3.077 g / cm 3 , with a specific surface area of 358m 2 / kg, the main components are CaO, SiO2, Fe2O3 and Al2O3, and the main minerals are tricalcium silicate, dicalcium silicate, tricalcium aluminate and tetracalcium aluminoferrite.
7. The road subgrade filler as claimed in claim 6, characterized in that: The persulfate gypsum slag cement is added by external mixing method, and the content ranges from 6% to 15%.
8. The road subgrade filler as claimed in claim 6, characterized in that: The first modified phosphogypsum and aeolian sand are used as aggregates, and the proportion of aeolian sand in the aggregate is between 0.25 and 0.
75.
9. The method for preparing a road subgrade filler prepared by synergistic solidification of phosphogypsum and aeolian sand according to any one of claims 2 to 8, characterized in that: The following steps are involved: S1. Preparation of aggregate: crush the larger agglomerates in the wet-ground modified phosphogypsum, put them into an oven and dry them at 55°C to 60°C for 48h to 60h, and then pass them through a 0.6mm pore size sieve to obtain the treated phosphogypsum; Aeolian sand within different particle size ranges is screened, and after weighing according to the determined aeolian sand particle group gradation, the aeolian sand is mixed evenly with the graded particle group to obtain aeolian sand; S2. Preparation of persulfated phosphogypsum slag cement: wet-ground modified phosphogypsum, granulated blast furnace slag powder and ordinary Portland cement are mixed according to a preset ratio, and then put into a cement paste mixer to ensure that the total water-cement ratio is 0.42-0.47 and stirred to obtain persulfated phosphogypsum slag cement; S3. Dry mixing: Mix the aggregate phosphogypsum and aeolian sand evenly according to a preset ratio, pour into a mortar mixer and stir for 3 to 7 minutes to obtain a first mixture. S4. Wet mixing: Pour persulfate gypsum slag cement and water into a mixer according to a preset ratio, stir at a speed of 500 r / min to 700 r / min for 5 to 10 minutes until uniform, to obtain a second mixture. S5, molding and curing: spreading and compacting the second mixture obtained in step S4, and performing heat preservation and moisture preservation curing to obtain the road subgrade filler in which the phosphogypsum and aeolian sand are synergistically solidified.
10. The preparation method according to claim 9, characterized in that: In step S4, the optimum moisture content of 15.064% to 16.274% and the maximum dry density of 1.717 g / cm2 determined by the compaction test are as follows: 3 ~1.784g / cm 3 Weigh the water.
Citation Information
Patent Citations
A low-shrinkage, high-strength aeolian sand roadbed material and its preparation method
CN110204299B
Sulfate resistant ground granulated blast furnace slag, sulfate resistant cement, and method of production of same
CA2735256A1
Curing agent for curing aeolian sand, method for curing aeolian sand and aeolian sand subbase
CN109437716A
Phosphogypsum supersulfide slag cement stable layer, phosphogypsum-based cementing material thereof and preparation method of phosphogypsum supersulfide slag cement stable layer
CN111848080A
Phosphogypsum-based regenerated aggregate as well as preparation method and application thereof
CN116283001A